Workshops on Business Informatics Research BIR 2011 International Workshops and Doctoral Consortium, Riga, Latvia, October 6, 2011 Revised Selected Papers - Niedrite, Laila; Strazdina, Renate; Wangler, Benkt; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed and revised proceedings of the workshops and the doctoral consortium co-located with the 10th International Conference on Perspectives in Business Informatics Research (BIR), held in Riga, Latvia, in October 2011.The four workshops focused on Information Logistics and Knowledge Supply for Viable Enterprises (ILOG 2011), Alignment of Business Processes and Security Modeling (ABPSM 2011), Intelligent Educational Systems and Technology-Enhanced Learning (INTEL-EDU 2011), and User-Oriented Information Integration (UOII 2011). The two best papers from the doctoral consortium are also included.
Keywords: Computer science; Information storage and retrieval systems; Information systems; Education; Management information systems; Computer Science; Computer Appl. in Administrative Data Processing; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Business Information Systems; Production/Logistics/Supply Chain Management; Computers and Education